Marine enzymes and specialized metabolism. - Moore, Bradley S. (Bradley Scott), 1966- (Methods in enzymology, 2018)
Marine enzymes and specialized metabolism - Part B, Volume 605 in the Methods in Enzymology series, highlights experimental methods on diverse marine enzymes involved in the construction of bioactive natural product molecules. Unique sections in this new release include discussions on polysaccharide-degrading enzymes from marine gastropods, radical SAM epimerases from sponge microbes, DMS/P demethylase in bacteria, reconstitution of particulate methane monooxygenase into membrane mimetics, the structure and function of cyanobactin enzymes, marine cyanobacterial polyketide beta-branching enzymology, marine cyanobacterial PKS-NRPS enzymology and structural biology, biochemical profiling of DMSP lyases, and more. Subject not before covered in a methods bookAuthority and expertise of the contributors